2015
DOI: 10.1371/journal.pone.0140382
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Occupational Needle Stick and Sharps Injuries among Hospital Healthcare Workers in Bale Zone, Southeast Ethiopia

Abstract: BackgroundNeedle stick and sharps injuries are occupational hazards to healthcare workers. Every day healthcare workers are exposed to deadly blood borne pathogens through contaminated needles and other sharp objects. About twenty blood borne pathogens can be transmitted through accidental needle stick and sharp injury. The study was conducted to determine the lifetime and past one year prevalence of needle stick and sharps injuries and factors associated with the past one year injuries among hospital healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
62
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 13 publications
13
62
7
2
Order By: Relevance
“…Opposite to the conclusion by Bekele et al [16], our study revealed that there was no statistically significant association between HCP work experience and rate of sharps injury. Our finding also supported by a study conducted in Northern Ethiopia [20] where work experience did not affect the risk of sharps injury.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Opposite to the conclusion by Bekele et al [16], our study revealed that there was no statistically significant association between HCP work experience and rate of sharps injury. Our finding also supported by a study conducted in Northern Ethiopia [20] where work experience did not affect the risk of sharps injury.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the prevalence rate in our study was higher than the study report by Mbaisi et al [10] in Kenya, Gessessew and Kahsu [26] and Bekele et al [16] in Ethiopia. This inconsistency may be due to the difference in the operationalization of sharps injury, study population, the number of HCP in the facility, different work environment and culture and availability of resources [20].…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations